The adoption of mechanization, labour productivity and household income: Evidence from rice production in Thailand - Orawan Srisompun; Thanaporn Athipanyakul; Somporn Isvilanonda (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2019)
The planning of mechanization requires the quantitative assessment of a mechanization index and the impact of this index on agricultural yield and economic factors. The purpose of this paper is to investigate the effect of the adoption of agricultural mechanization and scale production on labour productivity and the generation of income for farmers. Cross-sectional data for jasmine rice production by 569 households in 1,003 plots in the north eastern part of Thailand in 2017 were employed. The study found that the average rice planting workforce and labour productivity have an inverse relationship with planted area, while large farms have the highest ratio for machine labour to workforce. The rice yield, labour usage and labour productivity of the farmers varied by mechanization level (ML) and farm size while different levels of Machinery Owned labour (MO) have no effect on rice yield. Therefore, there are three main suggestions: 1) performing land consolidations, since applying a production strategy with large rice paddies may increase labour productivity and the net profit of rice famers; 2) improving the quality of machinery for use in rice production in Thailand, especially the performance of the machinery to prevent losses during harvest; and 3) increasing the mechanization level to 50-75%, which could also increase labour productivity and net returns.
Keywords: Q12; Q16; Q18; 330; Family labour; Farm size; Hired labour; Multivariate analysis-of-variance; Pillai's statistics; Production cost; Rice yield; Small farm